Here’s the TRIQ: The Tromsø Interest Questionnaire Based on the Four-Phase Model of Interest Development - Dahl, Tove I.; Nierenberg, Ellen (Frontiers in Education, 2021)
The Tromsø Interest Questionnaire (TRIQ) is the first suite of self-report subscales designed for focused investigations on how interest is experienced in relation to Hidi and Renninger’s four-phase model of interest development. In response to the plethora of varied interest measures that already exist in terms of theoretical grounding, form, and tested quality, the TRIQ subscales were designed with a consistent form to measure general interest, situation dependence, positive affect, competence level, competence aspirations, meaningfulness, and self-regulation answered in relation to some object of interest. Two studies testing the subscales’ performance using different objects of interest (self-chosen “object-general,” and prespecified “object-specific”) provide evidence of the subscales’ internal consistency, temporal reliability, and phase-distinguishing validity. Patterns across the two studies demonstrate that the TRIQ is a sufficiently reliable and valid domain-tailorable tool that is particularly effective at distinguishing phase 1 (triggered situational) from phase 4 (well-developed individual) interest. The findings raise interesting questions for further investigation about the distinction and distance between all interest phases, the push-pull factors that influence how interests evolve and additional subscales to add to the suite.